(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The Independent Curriculum is a transformative policy in the Indonesian education system that requires teachers not only to understand the curriculum conceptually but also to be able to implement it effectively in learning. This study aims to analyze teachers’ understanding of the basic concepts of the Independent Curriculum and its implementation practices at MAN Kota Surabaya. The study used a qualitative approach with a case study design. The research data sources consisted of primary data obtained through in-depth interviews and learning observations of MAN Kota Surabaya teachers, as well as secondary data in the form of curriculum documents, teaching modules, and relevant literature. Data collection was carried out through observation, semi-structured interviews, and documentation. The data obtained were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. The results showed that teachers have understood the basic principles of the Independent Curriculum and implemented them through deep learning, Problem-Based Learning (PBL), and Project-Based Learning (PJBL) approaches. This implementation encourages increased student activeness, critical thinking skills, collaboration, and problem-solving skills. Research findings indicate that the successful implementation of the Independent Curriculum in madrasas is supported by teachers’ good understanding of the curriculum and their ability to integrate learning with Islamic values ​​that are characteristic of madrasas.